Tren Penelitian Konseling Dalam Pendidikan Inklusif di Indonesia: Analisis Konten - Amanah, Siti (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research aims to investigate the trends, in counseling studies related to education in Indonesia. The study utilizes content analysis as a method to systematically review papers from national journals over the last twelve years. By exploring the frequency and themes of counseling research topics methodologies employed and outcomes this research offers an overview of how counseling practicesre being incorporated and advanced in inclusive educational environments. There are around 29 articles published in national journals accredited at SINTA. These articles specifically discuss research on counseling and its relationship to inclusive education. The results show a growing interest in education focusing significantly on developing counseling practices, training teachers and supporting students. This study emphasizes the advancements achieved far and points out areas for exploration and future research directions contributing to the improvement of counseling services within inclusive education, in Indonesia.